Histological observations on spermatogenesis in winter flounder, Pleuronectes americanus Walbaum, from Conception Bay, Newfoundland, Canada - Moulton, Sonya M; Burton, Margaret PM (Canadian Journal of Zoology, 1999)
Male winter flounder, Pleuronectes americanus Walbaum, collected from Conception Bay, Newfoundland, from late July to October 1997 were studied to provide histological insight into the cycle of spermatogenesis. The sequence of stages followed the same general pattern as that described for a variety of other teleost species, beginning with mitotic proliferation of reserve spermatogonia. Spermatogenesis was found to be very rapid compared with reports for other seasonal spawners. The onset of spermatogenesis, as indicated by the appearance of mitotic figures, occurred during September and the process was completed just over a month later. Therefore, sperm were present in the testes at least 6 months prior to the usual time of spawning. Possible reasons why spermatogenesis is completed so long before spawning in P. americanus are discussed.